2012
DOI: 10.3390/agriculture2030244
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Chokeberry Bioactive Polyphenols during Juice Processing and Stabilization of a Polyphenol-Rich Material from the By-Product

Abstract: Chokeberries (Aronia melanocarpa) are nowadays believed to exhibit potential cardioprotective and antidiabetic effects principally due to their high content in bioactive phenolic compounds. The stability of the phenolic compounds was studied during different stages of a juice production line and a method for the valorization of pomace was evaluated. Samples were taken from a commercial juice production plant, extracted and analyzed for phenolic constituents and antioxidant potential. Prototypes of functional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 35 publications
8
49
1
2
Order By: Relevance
“…Nevertheless, chokeberry juice contains several classes of phenolic compounds which in combination might differently affect the lipase activity due to the different interaction between them as well as with other juice components. The results of qualitative and quantitative analyses of low molecular phenolic compounds by UPLC-MS and HPLC methods allowed to conclude that all most active juices had the same phenolic profile (Table 3), which was in accordance with the data published [9,34]. The major low molecular phenolic compounds of chokeberry juice were chlorogenic acids such as 3-and 5-O-caffeoylquinic acid.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Nevertheless, chokeberry juice contains several classes of phenolic compounds which in combination might differently affect the lipase activity due to the different interaction between them as well as with other juice components. The results of qualitative and quantitative analyses of low molecular phenolic compounds by UPLC-MS and HPLC methods allowed to conclude that all most active juices had the same phenolic profile (Table 3), which was in accordance with the data published [9,34]. The major low molecular phenolic compounds of chokeberry juice were chlorogenic acids such as 3-and 5-O-caffeoylquinic acid.…”
Section: Discussionsupporting
confidence: 75%
“…The mean size of proanthocyanidin molecules described by their mDP in the chokeberry juices tested was very diverse and ranged from 12 to 52, while for two more efficient juices was >40 (Table 2). For comparison, the mDP value for chokeberry juice obtained from heated fruits followed by decantation of raw juice was 24 [34]. The very high mDP values obtained in this study for juice brands 1 and 2 may indicate lack of enzyme treatment of chokeberry mash during fruit processing as well as decantation or filtration process of raw juice.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The total phenolics contents of CCJ and FCJ were similar (p = 0.79), showing that processes included in the production of the commercial juice (pectinase treatment, filtration) did not influence the phenolics of the juice. The obtained results were in accordance with the results of Mayer-Miebach et al 17 The contents of total phenolics in WCE and MCE, expressed as mg GAE per g of WECE dry weight (DW), were 4 and 2.5 times lower, respectively, than phenollics content in the juices, calculated on DW. It could be concluded that the phenolics present in 100 mL of juice could be provided with at least 35 g of the investigated extract, indicating that the extraction process should be further optimized and/or prioritizing juice as the optimal source of chokeberry phenolics in future clinical studies.…”
Section: Total Phenolics Contentsupporting
confidence: 93%